Computer integrated design and manufacturing of patient specific lower limb orthoses through 3D reconstruction / Morshed Alam - Morshed , Alam (2014)
Patients with stroke and other neurological disorders like trauma, multiple sclerosis (MS) experience different lower limb disabilities due to various damages in neuromuscular system. Orthotic devices are prescribed to compensate muscle weakness, prevent unwanted movement of the impaired limb. Design and manufacturing methods of lower limb orthoses involve manual techniques e.g. casting and moulding of the limbs to be treated, vacuum forming etc. Such methods are time consuming, require skilful labour and often based on trial and error rather than systematic engineering and evidence based principles. In recent years, 3D scanning and reconstruction of medical images facilitate making 3D computer models of lower limb, which allows computer aided design (CAD) tools to be incorporated in orthotic design. All these approaches rely on the external model of lower limb and limited to single piece plastic ankle foot orthosis (AFO) only. To design orthosis with articulated joint, precise alignment of anatomical joint and mechanical axis is necessary. However, it is difficult to infer joint axes from external models as it is partially specified by skeletal structure. In our research, a design approach for custom knee ankle foot orthosis and ankle foot orthosis with commercially available joints has been demonstrated, which involves skeletal structure of lower limb for locating anatomical axes to ensure accurate alignment of orthotic mechanical joint. CAD models of the orthotic components were developed based on the 3D models of a healthy subject’s lower limb, which were developed through 3D reconstruction. Components of the orthotics were fabricated by rapid prototyping and machining to demonstrate the new approach. The fabricated orthoses were evaluated by a certified orthotist and the performance of the custom made AFO was compared statistically with a pre-fabricated AFO with similar ankle joint. The manufacturing process requires approximately 50% lesser time to develop AFO and 70% lesser time to develop KAFO compared to Brace and Limb laboratory of University Malaya. Unlike traditional approaches, the design technique facilitates exact positioning of articulated joint. The developed orthoses are light in weight, comfortable and easy to don and doff. Biomechanical test implies that the fabricated AFO provides better range of motion than a pre-fabricated AFO with same ankle joint. Although the custom AFO allowed significantly higher plantar flexion during pre-swing compared to pre-fabricated AFO condition (MD = 1.734, MSD = 1.55), the subject’s ankle required to generate significantly higher power with the pre-fabricated AFO (MD = 0.141, MSD = 0.035). These findings suggest that the subject had to overcome higher resistance with pre-fabricated AFO compared to custom made AFO. Simultaneous viewing of exterior and skeletal geometry might help the clinicians modify the design to enhance performance of the orthotic device.